English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

-2x + 3y = 4

-3x + 1y = 13

2007-06-12 05:55:58 · 8 answers · asked by Aaron l 1 in Science & Mathematics Mathematics

8 answers

Isolate "x" or "y" in either equation. let's isolate "y" in the 2nd equation.

First: add 3x with both sides (when you move a term to the opposite side, always use the opposite sign).

2. - 3x + y = 13
- 3x +3x+ y = 13+3x
y = 13+3x

Sec: substitute "13+3x" with "y" in the 1st equation.

1. -2x + 3y = 4
-2x + 3(13+3x) = 4
-2x + 3(13)+3(3x) = 4
-2x + 39+9x = 4
7x + 39 = 4 (subtract 39 from both sides).
7x + 39-39 = 4-39
7x = -35 (divide both sides by 7).
7x/7 = -35/7
x = -5

Third: substitute -5 with "x" in the 2nd equation.

2. -3x + 1y = 13
-3(-5) + 1y = 13
15 + y = 13 (subtract 15 from both sides).
15 -15+ y = 13-15
y = -2

Solution set: (-5, -2)

2007-06-12 07:44:05 · answer #1 · answered by ♪♥Annie♥♪ 6 · 2 0

Use 2nd eqaution to get y = 13+3x
Now substitute into 1st equation getting:
-2x +3(13+3x) = 4
-2x + 39 +9x = 4
7x = - 35
x = -5
-2(-5) +3y = 4
10 + 3y = 4
3y = -6
y = -2

2007-06-12 13:04:12 · answer #2 · answered by ironduke8159 7 · 0 0

Solve the second equation for y:
y = 13 + 3x

Plug that back into the first equation:
-2x + 3(13 + 3x) = 4

Distribute the 3:
-2x + 39 + 9x = 4

Combine like terms:
7x + 39 = 4

Subtract 39 from both sides:
7x = -35

Divide both sides by 7:
x = -5

Plug that back into the second equation:
-3(-5) + y = 13
15 + y = 13

Subtract 15 from both sides:
y = -2

2007-06-12 13:01:26 · answer #3 · answered by Joy M 7 · 0 1

-2x + 3y = 4
-3x + 1y = 13 therefore y=3x+13

substitute into first equation
-2x + 3(3x+13)=4

solve for x

2007-06-12 12:59:56 · answer #4 · answered by czwtrpolo2 2 · 1 2

Multiplying through to get coefficient of x equal:

-6x + 9y = 12
-6x + 2y = 26

Subtract the second from the first:

7y = -14 => y = -2

Sub this back into the second equation:

-3x - 2 =13
-3x = 15 => x = -5

2007-06-12 13:01:04 · answer #5 · answered by Daniel A 2 · 1 1

you have to isolate one of the variable usually its y, but doesnt matter, so work backwards to get y alone.

-2x + 3y =4 becuase we add 2x to both sides we get
3y = 4 + 2x then we divide by 3 to get y by itself
y = (4 + 2x) / 3

we can then plug a number in for x and get an answer for y plug in 3 random numbers to draw the line. I will let you try the last one and feel free to ask me anyother questions i will keep an eye this question

2007-06-12 13:03:23 · answer #6 · answered by CT 1 · 0 2

2nd equation equals...y = 3x +13...substitute in to the first:

-2x + 9x + 39 = 4
7x = -35
x = -5

Solve for y
y = 3*-5 +13
y=2

2007-06-12 13:00:18 · answer #7 · answered by gebobs 6 · 0 3

do you want to find - what x and y =??
y = -2
and
x = -5
I think so anyway mind still hurts from maths GCSE yesterday :D and i dont have a calc - which you prob didnt need but im a bit doopy!
Em xxx

2007-06-12 13:02:35 · answer #8 · answered by Emily-Pip 2 · 0 1

fedest.com, questions and answers